VALIDITY OF LEARNING MODEL FOR IMPROVING JUNIOR HIGH STUDENTS’ ARGUMENTATION SKILLS AND SCIENCE CONCEPT UNDERSTANDING - Rini N. Astuti; Suyono -; Mohamand Nur (PROSIDING SEMINAR KIMIA, 2015)
Argumentation is a very important process in leaning science. Learning science that involve argumentation can train students to be able to scientifically argue about a concept, defend their arguments, and refuse others by giving supporting evidence also logical reasons. From few researches been done, obtained that learning which involve argumentation can improve students’ argumentation skills and concept understanding. This research used to get learning model that can improve junior high students’ argumentation skills and science concepts understanding. A model that developed is focusing on 4 aspects of argumentations skills are, (1) deciding claim, (2) giving supporting evidence according to the claim, (3) organize reason, (4) organize counter-argument. This model is developed based on validation result by science learning expert through Focus Group Discussion (FGD) program. Two results obtained from that program. First, the developed model has a goal to increase argumentation and science concept understanding. Second, learning syntax (teacher and student-activities) consist of five phases, which are orientation, exploration, pre-argument, argument and counter-argument, and last reflection.